2020
DOI: 10.1109/access.2020.2981169
|View full text |Cite
|
Sign up to set email alerts
|

A Cooperative Lane Change Model for Connected and Automated Vehicles

Abstract: The emerging technology of vehicle-to-vehicle (V2V) communication, vehicle-toinfrastructure (V2I) communication makes it possible for vehicles to sense the environment information, which can be exploited to assist the vehicle in cooperative motion planning. In this paper, we focus on the cooperative trajectory planning of lane changes for connected and automated vehicles (CAVs). The proposed model considers the traffic scene with multiple mandatory lane change demands and completes the trajectory planning for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In this subsection, we evaluate the effectiveness of the proposed multi-objective reward function with the driving comfort in Eqn. (3). Figure 5 shows the acceleration and deceleration of the AV with or without the comfort measurement defined in Eqn.…”
Section: Verification Of Driving Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…In this subsection, we evaluate the effectiveness of the proposed multi-objective reward function with the driving comfort in Eqn. (3). Figure 5 shows the acceleration and deceleration of the AV with or without the comfort measurement defined in Eqn.…”
Section: Verification Of Driving Comfortmentioning
confidence: 99%
“…However, there exists a huge challenge in the task of high-level decision-making in AVs due to the complex and dynamic traffic environment, especially in mixed traffic co-existing with other road users. Lane changing is one of the largest challenges in the high-level decision-making of AVs, which has significant influences on traffic safety and efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies [10], [11], [12] demonstrated wireless V2V communication protocols for cooperative maneuvering systems for autonomous vehicles to enable them to perform complex road maneuvers through message exchange. The authors of [13] and [14] proposed a Cooperative Lane Changing solutions for AVs based on V2V and V2I connections to improve motion planning and thus improve traffic operations. The study in [15] investigated cooperative vehicle parking system via V2V wireless communication to allow vehicles to find and select parking spaces.…”
Section: Related Workmentioning
confidence: 99%
“…In the mixed traffic, there are few studies on the influence of lane-changing behavior on traffic flow, and more researches focus on the study of lane-changing behavior of autonomous vehicles. e research studies on lanechanging behavior of autonomous vehicles mainly include lane-changing intention [24,25], lane-changing decision [26,27], cooperative lane-changing between front and rear vehicles [28][29][30][31], and lane-changing position [32]. Research studies use human behavior as the research basis to construct human-like behavior models.…”
Section: Introductionmentioning
confidence: 99%